AMERICAN PRAGMATISM AS PORTRAYED IN MIRANDA PRIESTLY CHARACTER IN THE DEVIL WEARS PRADA - Wijayanti, Dyah Kartika; Hawasi, Hawasi (Universitas Gunadarma, 2019)
The aim of this research is to find out the pragmatism values as portrayed in the character of Miranda Priestly in The Devil Wears Prada movie script. The research method employed is a qualitative method and used philosophical approach to explain pragmatism as an ideology of America. The finding implies that Miranda Priestly has characteristics such as practical, realistic, instrumental and materialistic indicating that she is a pragmatic person